Effect of different treatments on grain weight and protein content of the grains from different ear positions for barley - YIN Chen; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版)
The effect of agronomic factors on grain weight and protein content of the grains from different ear positions (top, middle and bottom) in barley cultivars 92-11 and Xiumai-3 was studied. It was shown that grain weight of middle-positioned grains was the highest, and that of top-positioned grains was the lowest in all different treatments. Meanwhile the difference between two cultivars was significant, 92-11 being higher than Xiumai-3. Timing of nitrogen application significantly affected protein content of the grains from different ear positions, and protein content increased with heavy N application at late stage. The increase was mainly caused by higher protein content in bottom-and middle-positioned grains. In addition, heavy N application at late stage caused a significant increase in middle-and bottom-positioned grain weight. The population size after heading markedly affected grain weight and protein content and, with the increase of spike number, grain weight of bottom-and middle-positioned grains reduced, but their protein content increased. There was a substantial difference between two cultivars in the response of protein content to spike number, and greater changes occurred in bottom positioned grains for 92-11 and in top positioned grains for Xiumei 3. Deletion of middle-positioned grains significantly increased weight of top-positioned grains and removal of flag leaf resulted in the weight reduction of both middle-and bottom-positioned grains. In addition, reduction of both source and sink induced increase in protein content of grains.